PENENTUAN NILAI MANFAAT EKONOMI TAMAN NASIONAL GUNUNG GEDE PANGRANGO SEBAGAI TEMPAT REKREASI - Rabayu Supriadi (Jurnal Penelitian Hasil Hutan, 1995)
Indonesian economic growth as reflected by increase of per capita income, improvement of physical infrastructure and facilities as well as socio-economic and political condition have resulted in the increase of recreation demand. The Gede Pangrango Nasional Park is an example of such a forest recreation site with indigenous and exotic flora and fauna, its natural landscape of great beauty and other attractiveness and facilities could stimulate the visitors. As the park is easily reached from the surrounding cities like Jakarta, Bogor, Cianjur, Sukabumi and other cities of Java it seems that demand for recreation in this park is considerably increasing.The objectiveof this study are to get a better insight into the socio-economic aspect of the recreation in the park and to demonstrate the use of internationally accepted method, namely Travel Cost Method, to measure the economic value of the park.The demand equation and demand curve, the annual benefits (consumer's surplus). and the present value of the park have been estimated. The application of the Travel Cost Method (TCM) as a result of this study indicates that the participation rate of the recreation is 2,238 visitor per million inhabitants. The relationship between participation rate (V/P) and directc travel and time cost (TC) can be derived from the demand equation: V/P= -62,5 + 1675240/ TC2 with determinant coefficient, R2= 0.6362. This equation gives the estimated value of the annual benenfits of Rp 1.389 billion or an estimated value of Rp 17,370,- per visit. This is the amount of visitors' willingness to pay on average beyond what they actually pay. This amount gives also a present value of the park of Rp 25,55 billion as the economic value of the park providing recreational opportunity. This figure is based on the assumption that actual visit to the park continues to grow with 6.5 percent annually during the next 30 years and a discount rate of 10 percent, the time value is 50 percent of the hourly income, and are excluded extra cost likefor lodging and the equipment of tents. There will be upward bias due to multi-site visit, and downward bias because of visitors measure rather than day-visit.The expected increase in the number of visitors will place a tremendous pressure on the management of the park. Therefore,improved planning and management activities are needed. This will require an increase of the budget for planning and management to prevent a degradation of the attractiveness of die park. A degradation will mean that the park will lose its high economic value. Further study is recommended to get a more accurate figure of the economic value of the park by inclusion of substitute recreational site, multi-site visit, on-site travel time cost, and all expenses of visitors spent in the estimation of the benefits.